Factor analysis of the relationship of curiosity and device addiction through motivation to digital literacy in the context of smart learning - Yeka Hendriyani; Muhammad Anwar; Hendra Hidayat; Elsa Sabrina; Pardjono Pardjono; Erni Marlina Saari (Universitas Negeri Yogyakarta, 2023)
This research aims to determine the relationship between curiosity factors and device addiction with digital literacy motivation in the context of smart learning. This qualitative study involves a sample of 228 students majoring in Electronics Engineering Education at Universitas Negeri Padang. The data collection technique was carried out using a questionnaire with a Likert scale using the saturated sampling method. Structural Equation Modeling (SEM) analysis was used to evaluate the measurement model of the research questions. The results showed that digital literacy skills are influenced by three main factors: curiosity, gadget addiction, and app addiction. The findings offer valuable insights for curriculum development, especially in improving digital literacy among electronic engineering education students preparing to face the challenges of the Industrial Revolution 4.0 era.